SIFO 1988: Swedes and the EC - Swedish Institute of Public Opinion Research; Tvärkontakt (magazine) (Swedish Institute of Public Opinion Research, 1993)
In this study carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of Tvärkontakt, an industrial conference, the respondents were asked about their opinion on the development of the cooperation between the Soviet Union and Western Europe, and USA and Western Europe within the next five years; interest to follow what happens within the EC; the effect of a Swedish EC-membership on areas such as standard of living, the protection of environment and the security of the country; attitudes toward Swedish companies buying companies in other countries and vice versa; the development of standard of living in Sweden compared with other countries; Swedish school education, medical care and pensions in comparison with the EC-countries; number of jobs in Sweden if Sweden joins the EC; attitude toward the free labour market within the EC; the feeling of being an Europena vs. being a Swede; opinion on a Swedish EC-membership before year 2000. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.

SIFO genomförde denna undersökning på uppdrag av näringslivskonferensen Tvärkontakt under perioden 24-30 maj 1988. Frågorna ingick i SIFO-buss 88084 och utfördes i form av telefonintervju.
Respondenterna fick ange hur man trodde att samarbetet mellan Sovjetunionen och Västeuropa, respektive USA och Västeuropa, skulle komma att utvecklas under den närmaste femårsperioden; det egna intresset för vad som händer inom EG och vad ett svenskt EG-medlemskap skulle innebära för levnadsstandarden, skyddet av miljön och säkerheten för Sverige som nation; åsikter om det är bra eller dåligt för Sverige att svenska företag köper företag i andra länder respektive att utländska företag köper företag i Sverige. Respondenterna fick även ange om man trodde levnadsstandarden i Sverige ökat snabbare eller långsammare under de senaste 15 åren än i andra industriländer i västvärlden, USA, Japan, Tyskland, England, Finland respektive Danmark. Därutöver fick man ange om man trodde Sverige var bättre eller sämre än länderna inom EG när det gällde utbildningen, sjukvården eller pensionerna för de äldre och om man trodde Sverige har mycket eller lite att lära av länderna i EG resp. lära ut till länderna i EG. Andra frågor gällde inställningen till den fria arbetsmarknaden inom EG, om man någon gång i första hand kände sig som europé och inte som svensk, och vid vilken tidpunkt man trodde Sverige skulle gå med i EG. Bakgrundsvariabler inkluderar uppgifter om kön, bostadsort, ålder, svenskt medborgarskap, sysselsättning, arbete inom privat eller offentlig sektor, fackföreningstillhörighet, om man brukar rösta i riksdagsvalet, bästa parti och vilket parti man röstade på i riksdagsvalet 1985.
SIFO 1988: Svenskarna och EG
Keywords: International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap